Localized delivery of immunosuppressive regulatory T cells to peripheral nerve allografts promotes regeneration of branched segmental defects. (July 2019) - Santos Roballo, Kelly C.; Dhungana, Subash; Jiang, Zhongliang; Oakey, John; Bushman, Jared S.
Abstract: Segmental injuries to peripheral nerves (PNs) too often result in lifelong disability or pain syndromes due to a lack of restorative treatment options. For injuries beyond a critical size, a bridging device must be inserted to direct regeneration. PN allografts from immunologically incompatible donors are highly effective bridging devices but are not a regular clinical option because of the expense and health risks of systemic immunosuppression (ISN). We have developed a method to deliver a single administration of ISN localized around a PN allograft that circumvents the risks of systemic ISN. Localized ISN was provided by regulatory T cells (Tregs), a potently immunosuppressive cell type, that was delivered around a PN allograft with a poly(ethylene glycol) norbornene (PEGNB) degradable hydrogel. Tregs are released from the hydrogel over 14 d, infiltrate the graft, suppress the host immune response and facilitate regeneration of the recipient rats equal to the autograft control. Furthermore, this method was effective in a segmental PN defect that included a branch point, for which there currently exist no treatment options. These results show that localized delivery of immunosuppressive cells for PN allografts is an effective new strategy for treating segmental PN defects that can also be used to regenerate complex nerve structures.